Knowledge, Attitudes, and Practices Regarding Antibiotic Sales in Pharmacies in Medellín, Colombia 2023 - Daniel Ricardo Montes Colonia; Daniela Ramírez Patiño; Luis Felipe Higuita-Gutiérrez (Antibiotics, 2023)
Objective: Describe the knowledge, attitudes, and practices regarding the sale of antibiotics in pharmacies in Medellín, Colombia. Method: A cross-sectional descriptive study was conducted in 277 selected pharmacies using a stratified sampling method with proportional allocation to represent all areas of the city. Knowledge, attitudes, and practices (KAPs) were assessed using a scale, analyzed with absolute and relative frequencies for each item, and represented in a global score ranging from 0 to 100, with a higher score indicating better KAPs. Data were analyzed using relative frequencies with 95% confidence intervals, the Mann-Whitney U test, the Kruskal-Wallis test, and linear regression. Results: Of the included pharmacies, 52.6% were chain pharmacies, 48.4% were attended by pharmacy assistants, and 59% of pharmacists had more than 5 years of experience. The median knowledge score was 70.8 (IQR 58.3–87.5), with 35.3% of pharmacists believing that antibiotics are effective in treating the common cold, 35.2% for treating COVID-19, and 29.4% considering them available for sale without a medical prescription. The attitude score was 53.3 (40.0–66.7), with 60.9% agreeing that prohibiting the sale of antibiotics without a prescription would decrease their sales. The practice score was 62.5 (40.0–79.2), with 65.4% of pharmacists stating that they sometimes sell antibiotics without a prescription due to patients struggling to obtain a medical consultation, 61.3% admitting to selling antibiotics without a prescription for urinary tract infections, and 41.3% for upper respiratory tract infections. Practices were predominantly influenced by pharmacy type (chain or independent) and, to a lesser extent, by knowledge and attitudes. Conclusion: Pharmacists in Medellín exhibit inadequate knowledge, attitudes, and practices regarding the use and sale of antibiotics without a medical prescription. These findings align with international evidence highlighting the need for educational and regulatory strategies promoting rational antibiotic use in pharmacies.